Right to Education; a Comparative Analysis of the Implementation of Universal Primary Education in Rural Areas of Uganda’s Eastern Region: Lessons From Similar Initiatives in Other African Countries. - Mary Monica Okumu (Uganda Christian University, 2024)
This paper explores the right to education, specifically focusing on universal primary education (UPE) and its effectiveness in rural areas of Eastern Uganda. Since Uganda gained independence in 1962, the Ministry of Education and Sports has overseen four education tiers: pre-school, primary, post-primary, and higher education. The Commission for the Review of Education Policy, established by the National Resistance Movement, recommended universal primary education. In 1996, the National Resistance Army initiated free education, aiming to provide access up to grade seven. However, UPE implementation faces challenges such as inadequate government commitment and coordination. This study, utilizing qualitative methods including literature reviews and stakeholder interviews, assesses UPE effectiveness and coordination mechanisms. It also considers international treaties on the right to education for comparative analysis. Additionally, the research compares Kenya's education system to identify strategies for enhancing UPE outcomes and realizing universal education rights for all children.